Evaluasi Sistem Pencahayaan Gedung Pendidikan Perkuliahan Sesuai Standar Nasional Indonesia (SNI) - Vicky Prasetia; Supriyono; Purwiyanto (Infotekmesin, 2022)
The lighting system is one of the aspects of assessing the function of the building. The building lighting system is included in the health aspect of the building. To achieve proper function, the building lighting system must meet the illumination value of each room according to the type of utilization in accordance with SNI 6197:2011, SNI 6197:2011, SNI 03-2396-2001, dan SNI 03-6575-2001. This study aims to analyze the lighting system in the Gedung Kuliah Bersama at the Politeknik Negeri Cilacap. This study uses a quantitative method by comparing the amount of light intensity based on field measurements, calculation results, and the SNI 6197:2011 standard. Based on the results of observations, data processing, and measurements, it was found that there were still some rooms in the Gedung Kuliah Bersama that did not meet SNI. Rooms that have fulfilled SNI include classrooms, library rooms, language laboratories, lecturer transit rooms, multipurpose rooms, terrace, and warehouses. It is necessary to carry out maintenance and repair of lamps for rooms that do not meet SNI. Maintenance and repair of lighting systems are carried out by replacing, adding, and/or repositioning lamps.